Object oriented systems development - Bahrami, Ali (Irwin/McGraw-Hill, 1999)
Covers O-O concepts, tools, development life cycle, problem solving, modeling, analysis, and design, while utilizing UML (Unified Modeling Language) for O-O modeling. UML has become the standard notation for modeling O-O systems and is being embraced by major software developers like Microsoft and Oracle.